Long-term osseointegration of laser-ablated hearing implants in sheep cranial bone - Johansson, Martin Lars; Shah, Furqan A.; Eeg-Olofsson, Måns; Monksfield, Peter; Thomsen, Peter; Palmquist, Anders (Frontiers in Surgery, 2022)
Osseointegration, the ability for an implant to be anchored in bone tissue with direct bone-implant contact and allowing for continuous adaptive remodelling, is clinically used in different reconstructive fields, such as dentistry, orthopedics and otology. The latter uses a bone conducting sound processor connected to a skin-penetrating abutment that is mounted on a titanium implant placed in the temporal bone, thereby acting as a path for transmission of the vibrations generated by the sound processor. The success of the treatment relies on bone healing and osseointegration, which could be improved by surface modifications. The aim of this study was to evaluate the long-term osseointegration in a sheep skull model and compare a laser-ablated implant surface with a machined implant. Commercially available 4 mm titanium implants, either with a machined (Wide Ponto) or a laser-ablated surface (Ponto BHX, Oticon Medical, Sweden), were used in the current study. The surfaces were evaluated by scanning electron microscopy. The implantation was performed with a full soft tissue flap and the osteotomy was prepared using the MIPS drill kit (Oticon Medical, Sweden) prior to installation of the implants in the frontal bone of eight female sheep. After five months, biopsies including the implant and surrounding bone tissue obtained, processed and analysed using histology, histomorphometry, scanning electron microscopy and Raman spectroscopy. The animals healed well, without signs of adverse events. Histomorphometry showed a large amount of bone tissue around both implant types, with 75% of the threaded area occupied by bone for both implant types. A large amount of bone-implant contact was observed for both implant types, with 67-71% of the surface covered by bone. Both implant types were surrounded by mature remodelled lamellar bone with high mineral content, corroborating the histological observations. The current results show that the laser-ablated surface induces healing similar to the well-known clinically used machined surface in ovine cranial bone. In conclusion, the present long-term experimental results indicate that a laser-ablated implant performs equally well as a clinically used implant with a machined surface. This, together with previously reported, improved early biomechanical anchorage, suggests future, safe and efficient clinical potential.